Activation of heat shock response improves biomarkers of NAFLD in patients with metabolic diseases. Issue 5 (19th May 2021) - Kondo, Tatsuya; Miyakawa, Nobukazu; Kitano, Sayaka; Watanabe, Takuro; Goto, Rieko; Suico, Mary Ann; Sato, Miki; Takaki, Yuki; Sakaguchi, Masaji; Igata, Motoyuki; Kawashima, Junji; Motoshima, Hiroyuki; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is often accompanied by metabolic disorders such as metabolic syndrome and type 2 diabetes (T2DM). Heat shock response (HSR) is one of the most important homeostatic abilities but is deteriorated by chronic metabolic insults. Heat shock (HS) with an appropriate mild electrical stimulation (MES) activates HSR and improves metabolic abnormalities including insulin resistance, hyperglycemia and inflammation in metabolic disorders. To analyze the effects of HS + MES treatment on NAFLD biomarkers, three cohorts including healthy men (two times/week, n = 10), patients with metabolic syndrome (four times/week, n = 40), and patients with T2DM ( n = 100; four times/week ( n = 40) and two, four, seven times/week ( n = 20 each)) treated with HS + MES were retrospectively analyzed. The healthy subjects showed no significant alterations in NAFLD biomarkers after the treatment. In patients with metabolic syndrome, many of the NAFLD steatosis markers, including fatty liver index, NAFLD-liver fat score, liver/spleen ratio and hepatic steatosis index and NAFLD fibrosis marker, aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio, were improved upon the treatment. In patients with T2DM, all investigated NAFLD steatosis markers were improved and NAFLD fibrosis markers such as the AST/ALT ratio, fibrosis-4 index and NAFLD-fibrosis score were improved upon the treatment. Thus, HS + MES, a physical intervention, may become a novel treatment strategy for NAFLD as well as metabolic disorders.